2008
DOI: 10.1159/000112590
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum IGF-I/GH Ratio Is Associated with Abnormal Glucose Tolerance in Acromegaly

Abstract: Background/Aims: Acromegaly is frequently accompanied with impaired glucose tolerance (IGT) and diabetes mellitus (DM). It remains unclear which factors determine the abnormal glucose tolerance status in acromegaly. In addition, diverse actions of GH and IGF-I in regulating glucose metabolism in acromegaly have not yet been well elucidated. The aim of this study was to investigate the factors associated with abnormal glucose tolerance in acromegaly. Subjects and Study Design: We conducted a retrospective cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 79 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…This could mean that the net effect in acromegaly reflects the balance between the direct and indirect insulin-antagonizing actions of GH and the insulin-sensitizing actions of IGF-I. This is in concordance with the observation that a low IGF-1/GH ratio is associated with abnormal glucose tolerance in acromegaly [13]. However, in clinical studies of patients with acromegaly, a stronger association has been demonstrated between insulin resistance and IGF-1 levels than with GH levels [14][15][16].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This could mean that the net effect in acromegaly reflects the balance between the direct and indirect insulin-antagonizing actions of GH and the insulin-sensitizing actions of IGF-I. This is in concordance with the observation that a low IGF-1/GH ratio is associated with abnormal glucose tolerance in acromegaly [13]. However, in clinical studies of patients with acromegaly, a stronger association has been demonstrated between insulin resistance and IGF-1 levels than with GH levels [14][15][16].…”
Section: Introductionsupporting
confidence: 80%
“…Some have found that both GH and IGF-1 correlate with insulin resistance evaluated by the homeostasis model assessment (HOMA) and area under curve for insulin [11], while others have concluded with a stronger association between levels of IGF-1 and insulin resistance than between levels of GH and insulin resistance [14][15][16]. On the other hand, IGF-1 has been suggested to have insulinsensitizing effects [12], and low IGF-1/GH ratio in subjects with acromegaly has been suggested indicative of abnormal glucose tolerance [13]. Generally, the scientific evidence of disturbed carbohydrate metabolism in subjects with acromegaly is broad [8-11, 13, 14, 16, 37-40, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Kasayama et al A few studies have addressed the issue of b-cell function in acromegaly. Among them, Kasayama et al (7) failed to demonstrate a correlation between b-cell function and GH or IGF1 levels, whereas Fukuoka et al (8) detected a weak correlation between IGI and IGF1 levels. Long-standing IR appears to cause b-cell 'exhaustion', which leads to impaired b-cell function and the development of type 2 DM in non-acromegalic subjects (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated impaired glucose metabolism in acromegaly, but it is unclear which clinical parameters (e.g. GH, IGF1) play a role in IR and/or impaired b-cell function in the disease (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 % ULN/GH reflects ratio of baseline IGF-1 % ULN and baseline GH levels. IGF-1 % ULN/GH is the value defined as the ratio of baseline IGF-1 % ULN level according to baseline GH level and this ratio is revised from previous literature data [25].…”
Section: Methodsmentioning
confidence: 99%